Survival Analysis of Multi-Drug Resistant Tuberculosis Patients in North Sumatra - Dessritina, Pesona; Nursal, Dien Gusta Aggraini; Syafrawati, Syafrawati (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background: The severity and ease of spread of MDR-TB have caused this disease to become an epidemic in various countries. WHO has also launched an international program